2016
DOI: 10.1007/s00595-016-1353-1
|View full text |Cite
|
Sign up to set email alerts
|

Additional surgery for non-curative resection after endoscopic submucosal dissection for gastric cancer: a retrospective analysis of 200 cases

Abstract: The risk of a residual tumor can, therefore, be estimated based on the histopathology of endoscopic submucosal dissection samples. Lymphovascular invasion appears to be a pivotal predictor of lymph node metastasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
42
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 23 publications
5
42
2
Order By: Relevance
“…In addition, LNM do not appear in many patients who undergo gastrectomy for deep submucosal invasive EGC, the rate of which is estimated to be 7.2–27.3% [8-13]. Despite these findings, the risk factors (RFs) for LNM in patients who undergo ER for deep submucosal invasive EGC has not been fully understood because the previous reports about such patients are single-institution studies with a small number of cases.…”
Section: Introductionmentioning
confidence: 81%
“…In addition, LNM do not appear in many patients who undergo gastrectomy for deep submucosal invasive EGC, the rate of which is estimated to be 7.2–27.3% [8-13]. Despite these findings, the risk factors (RFs) for LNM in patients who undergo ER for deep submucosal invasive EGC has not been fully understood because the previous reports about such patients are single-institution studies with a small number of cases.…”
Section: Introductionmentioning
confidence: 81%
“…In this category, until JGCA guidelines version 4, additional surgery was recommended for all patients as a result of the potential risk of LNM. However, the rate of LNM in such patients was only 5.2%–11.0% . Thus, this recommendation may have been excessive.…”
Section: Management After Er In Each Curability Categorymentioning
confidence: 98%
“…However, the rate of LNM in such patients was only 5.2%-11.0%. 38,[47][48][49][50][51][52][53][54][55][56][57][58][59][60] Thus, this recommendation may have been excessive. In the JGCA guidelines version 5, 13 the statement for the management of eCura C-2 was changed as follows: "Additional surgery is the standard treatment method, but clinicians should decide considering the patient's physical condition."…”
Section: Ecura C-2mentioning
confidence: 99%
“…The rate of LNM in patients who underwent additional surgery after noncurative resection of ER for EGC is reported to be 5.2% to 11.0%. 53,54,[57][58][59][60][61][63][64][65][66][67][68][69][70] Most reports are from Korea and Japan, and only one study has been reported from Western countries. 53 In this study, LNM after noncurative resection was shown in 8.3% of the patients (1/12), 53 which is similar to the rate of LNM (8.5%) in the largest study from Japan.…”
Section: Lnm In Patients With Additional Surgery After Noncurative Rementioning
confidence: 99%